Hirschman, Albert O., Essays in Trespassing, Cambridge University Press, 1981, 310 pp. - Hodara, Joseph (Estudios Demográficos y Urbanos, 1984)
Hirschman, Albert O., Essays in Trespassing, Cambridge University Press, 1981.